Soil and Vegetation Drive Sesquiterpene Lactone Content and Profile in Arnica montana L. Flower Heads From Apuseni-Mountains, Romania - Greinwald, Anja; Hartmann, Martin; Heilmann, Jörg; Heinrich, Michael; Luick, Rainer; Reif, Albert (Frontiers in Plant Science, 2022)
Arnica montana L. (AM, Asteraceae) is a perennial, herbaceous vascular plant species of commercial importance. The flower heads´ pharmacological properties are attributed mainly to sesquiterpene lactones (SLs), with phenolic acids and flavonoids also considered of relevance. The botanical drug is still partly collected in different European mountain regions. The SL content can be influenced by genetic factors and environmental conditions (altitude, temperature and rainfall). Surprisingly, the influence of the soil on SL-content have rarely been investigated. However, the soil determines the occurrence, distribution and overall fitness of AM. Equally, environmental factors are crucial determinants for the biosynthesis and fluctuations in plant secondary metabolites. Therefore, different abiotic (pH, C/N ratio, base saturation, cation exchange capacity) and biotic (species richness, vegetation cover) parameters need to be assessed as potential drivers of the variable content of AM´s secondary metabolites. Consequently, we developed an in situ experimental design aiming to cover a wide range of soil pH conditions. We detected and investigated different AM populations growing in grassland on acidic soils, on siliceous as well as calcareous geologies within the same geographical region and altitudinal belt. The total SL content and most single SL contents of the AM flower heads differed significantly between the two geologies. AM flower heads of plants growing on loam on limestone showed a significant higher total SL content than the flower heads of plants growing in siliceous grasslands. Furthermore, the SL contents were significantly correlated with geobotanical species richness and vegetation cover pointing towards an effect of species interactions on the production of SLs. Moreover, the ratios of the main SLs helenalin to dihydrohelenalin esters were significantly correlated to environmental parameters indicating that SL composition might be a function of habitat conditions. The findings of this study shed light upon the often ignored, complex interactions between environmental conditions and plant secondary metabolites. We highlight the importance of both abiotic and biotic habitat parameters for SLs in AM.